Study of The Effect Stuart and Prandtl Numbers on Diamond Nano Fluid Flowing Through Cylindrical Surface - Yolanda Norasia; Mohamad Tafrikan; Mohammad Ghani; Asmianto Asmianto; Indira Anggriani (Universitas Amikom Purwokerto, 2023)
Fluid flow problems can be constructed using applied mathematical modeling and solved numerically using computational fluid dynamics (CFD). Nondimensional variables, stream functions, and similarity variables are used to simplify the governing equations from Newton's law, and thermodynamics law. These equations consist of continuity equations, momentum equations, and energy. Backward Euler method numerically solves the equations. The results show that the smaller the influence of the given Stuart number and Prandtl number, the fluid velocity and temperature will increase. Diamond nano fluid with water base fluid moves faster and experiences an increase in temperature faster than engine oil base fluid. this is due to the thermo-physical heat capacity of the water base fluid being greater than that of the engine oil.